An Analysis of Factors Influencing Generation Z’s Interest in Using Digital Islamic Banking Services in Indonesia - Ifada Rahmayanti (Pt. Anagata Sembagi Education, 2026)
Digital Islamic banking is one of the financial sectors experiencing rapid growth in tandem with digital transformation and demographic shifts in Indonesia’s population. Generation Z, born between 1997 and 2012, dominates Indonesia’s population and represents a strategic target group for the development of digital-based Islamic financial services. Although the market potential is significant, the national market share of Islamic banking remains relatively low, resulting in a gap between demographic potential and the actual adoption rate of these services. This study aims to identify and analyze the factors influencing Generation Z’s interest in using digital Islamic banking services in Indonesia through a systematic literature review approach. A total of seventeen scientific articles published between 2022 and 2026 were collected, selected, and analyzed based on topic relevance, methodological quality, and relevance to the research variables. The results of the study indicate that technological factors such as perceived ease of use, performance expectations, and enabling conditions consistently have a positive and significant influence. Social influences and digital marketing were also found to be strong external determinants. Sharia financial literacy, both directly and as a moderating variable, contributed to increased interest. Conversely, evidence regarding the role of religiosity and brand image remains mixed and inconsistent across studies. These findings indicate that Generation Z’s preference for digital Islamic banking is driven more by functional value, practicality, and social environmental influences than solely by religious motives. This study is expected to serve as a reference for the Islamic banking industry and policymakers in designing more targeted strategies for acquiring young customers